MXene-embedded PEDOT: PSS hole-transport material for lead-free perovskite solar cells - Ling, Jin Kiong; Cuzzupè, Daniele T.; Ud Din, Muhammad Faraz; Stepura, Anastasiia; Burgard, Tom; Temitmie, Yekitwork Abebe; Majkova, Eva; Omastova, Maria; Jose, Rajan; Mende, Lukas Schmidt-; Azhar, Fakharuddin (American Chemical Society, 2024)
Improving the energy alignment between charge-transport layers and the perovskite is crucial for further enhancing the photovoltaic performance of tin-based perovskite solar cells (PSCs). Herein, the role of Ti3C2Tx MXene in a poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) hole transport layer (HTL) on the photovoltaic properties of PSCs is investigated as a function of its concentration. An improved perovskite film formation with reduced pinhole density and a more uniform contact potential difference is noted when MXene is embedded in the PEDOT:PSS HTL. The work function of the HTL is increased according to photoelectronic measurements, leading to a favorable energy alignment with the HOMO of PEA0.2FA0.8SnI3 perovskite. PSCs fabricated using a MXene-embedded PEDOT:PSS HTL delivered a power conversion efficiency (PCE) of 8.35% compared to 7.35% from the pristine counterpart, while retaining ∼90% of its initial PCE after 450 h of storage in a N2 atmosphere.